Carthami Semen Pharmacopuncture Combined with Electroacupuncture on Carpal Tunnel Syndrome: A Retrospective Case Series Study - Pyung-Wha Kim; Seon Choe; Kyungsun Han; Changsop Yang; Jinbok Lee; Sungha Kim; Minseop Shin (Korean Pharmacopuncture Institute, 2021)
While carpal tunnel syndrome (CTS) is the most common entrapment neuropathy affecting the wrist, resulting in substantial physical, psychological, and economic effects, there is no gold standard therapy for CTS. In this case series study, we aimed to report CTS patients treated with Carthami Semen Pharmacopuncture (CSP) and electroacupuncture (EA) showing improvements in their symptoms, and the combinatorial effects of CSP and EA. We collected medical records of CTS outpatients who received CSP and EA at Chuk-u Acupuncture & Moxibustion Korean Medicine Clinic from August 2017 to September 2018. The outcome measures were the visual analog scale (VAS) for pain, paresthesia, the Korean version of the Boston carpal tunnel questionnaire (K-BCTQ) score, and changes in nocturnal pain, Tinel sign, and Phalen's test. We included patient satisfaction at the completion of all treatments. 17 patients were included for this case series study. After treatment, VAS for pain decreased significantly from 50.41 ± 16.19 to 9.59 ± 9.46, VAS for paresthesia also decreased significantly from 63.50 ± 11.49 to 14.75 ± 12.97, and K-BCTQ symptom severity scale decreased from 2.48 ± 0.68 to 1.89 ± 0.70 (all p < 0.001). Nocturnal pain, Tinel signs, and Phalen's test showed improvements after all the treatments. All the patients reported favorable overall satisfaction with the treatments, and 69.23% wanted future pharmacopuncture treatments if CTS recurred. No complications were detected. The combination of CSP and EA could be an effective and safe option in treating CTS.